The brain drain phenomenon in the Muslim world - Abdul Razak, Mohd Abbas; Machouche, Salah (Department of Communication, AHAS-Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), 2022)
For many decades the Muslim world has been plagued by a number of national issues. Poverty, illiteracy, leadership crisis, political instability, economic crisis, etc. The brain drain phenomenon which is one of the many unsolved issues in most Muslim countries has not been given serious attention. Unless the Muslim world tackles this issue, it will not be able to witness any great development in the areas of science and technology. In a simplified manner, what is defined as a brain drain phenomenon, is the migration of experts, professionals and intelligentsia from Muslim countries to the developed nations in Europe and America. Research into this topic explains that brain drain happens for a number of reasons. We would like to highlight some of the underlying factors that cause the brain drain phenomenon to happen in the Muslim world such as economic crisis, political instability and opportunity for growth.